Two daughters of a lorry driver shared the convocation stage - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 1 November – It was a sweet memory for a couple of sisters to share the stage during the fourth session of the 12th UMP Convocation Ceremony held at the Sports Complex, Gambang Campus today.